2017
DOI: 10.3233/ais-170422
|View full text |Cite
|
Sign up to set email alerts
|

An open solution to provide personalized feedback for building energy management

Abstract: The integration of renewable energy sources increases the complexity in mantaining the power grid. In particular, the highly dynamic nature of generation and consumption demands for a better utilization of energy resources, which seen the cost of storage infrastructure, can only be achieved through demand-response. Accordingly, the availability of energy and potential overload situations can be reflected using a price signal. The effectiveness of this mechanism arises from the flexibility of device operation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…www.nature.com/scientificdata www.nature.com/scientificdata/ a personalised feedback system 19 and a measurement campaign in Austrian households 20 . We define one uniform distribution per appliance based on those time windows.…”
Section: Dataset Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…www.nature.com/scientificdata www.nature.com/scientificdata/ a personalised feedback system 19 and a measurement campaign in Austrian households 20 . We define one uniform distribution per appliance based on those time windows.…”
Section: Dataset Generationmentioning
confidence: 99%
“…While some appliances such as dishwashers are designed to have clear programmes of operation with a predictable end time, it is challenging to identify the most appropriate power consumption pattern for user-controlled appliances such as hair dryers and microwave ovens. We addressed this issue by incorporating expert knowledge into our measurement campaign, which is a result of studies related to a personalised feedback system for energy management in households 19 and conclusions drawn from the outcome of a measurement campaign in Austrian households 20 . Based on this knowledge, we adapted the residents behaviour during measurements, i.e.…”
mentioning
confidence: 99%
“…Further, management services are those that address specific functionalities of the smart home. Examples of such services can be those concerning the security and safety of inhabitants (for example the anti-intrusion alarms or the detection of gas leaks) [35] or those concerning energy efficiency of the home [65], such as those that control ventilation and solar panels for the energy production and those that control the appliances and lights to reduce energy consumption while satisfying the inhabitants' needs.…”
Section: Smart Homementioning
confidence: 99%
“…In the study reported in Monacchi et al [16], we analyzed the GREEND dataset to identify energy hogs and possible policies for improving overall efficiency, which can be summarized as:…”
Section: Analyzing Energy Use and Improving Awarenessmentioning
confidence: 99%